Good Corporate Governance and RUPS Decisions on Corporate Artificial Intelligence - Safyudi, Kathlina (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The rapid development of Artificial Intelligence (AI) and growing demands for sustainability have significantly reshaped corporate governance in Indonesia. AI enhances operational efficiency, improves decision-making processes, and enables data-driven strategies, while sustainability principles demand a balance between profit and social-environmental responsibility. This study examines the role of Rapat Umum Pemegang Saham (RUPS) in determining AI and sustainability policies through the application of Good Corporate Governance (GCG) principles. The research employs a normative juridical and doctrinal approach, with a descriptive-analytical method, to analyze primary, secondary, and tertiary legal materials. The study highlights that the GCG principles—transparency, accountability, responsibility, independence, and fairness—serve as a foundation for legitimizing and overseeing corporate policies. The RUPS, through these principles, plays a strategic role in ensuring that AI policies align with legal, ethical, and sustainable practices. However, challenges such as regulatory gaps, limited shareholder literacy, and potential ethical risks remain. The study concludes that integrating GCG principles into AI and sustainability policies is essential for achieving a corporate governance model that is legally sound, ethically responsible, and capable of balancing technological innovation with social and environmental goals. To strengthen the governance process, it is recommended that companies enhance shareholder education on AI and sustainability, develop comprehensive AI regulations, and form independent oversight committees within the RUPS.